Música e as emoções coletivas : um estudo de caso a partir dos jingles eleitorais das campanhas presidenciais de 2018 de Fernando Haddad (Brasil Feliz de Novo) e Jair Bolsonaro (Muda Brasil) - Caffarate, Melanie dos Santos (2020)
Music plays a key role in society and can be used as a strategic communication tool. In the political communication context, actors use discursive resources on their electoral campaigns to attain the vote. When those persuasive strategies embrace an emotional aspect, it is possible to infer that the objective is to sway the collective emotions. The starting point for this study is the idea that the music has the power to influence emotions and this source can be used as political communication strategies. However, it is not the objective of this study to infer that the composition of the electoral jingle is a determining factor for winning the elections, but it is part of the communication strategies. From analyzes performed with data displayed using the LIWC and Cyanite softwares, we could identify the emotional tone and the frequency of emotions communicated in the campaign jingles of Fernando Haddad and Jair Bolsonaro, in the 2018 presidential election campaign. The case study applies these tools to the research. In fact, both jingles have similar aspects because they are compositions of the same category. However, the strategies used to communicate some emotions and the emotional tone are evident, fact that shows the different communication goals of each political actor. It was found that the use of emotional factors in the compositions, in fact, is a means to assist in communication strategies with the aim of creating social bonds and introducing candidates into the collective imagination.